Auditory environments influence the link between Autistic traits and quality of life - R. Poulsen; D. W. Tan; P. F. Sowman; D. McAlpine; E. Pellicano (Scientific Reports)
Abstract Autistic people often report a heightened sensitivity to sound. Yet, research into Autistic people’s auditory environments and their impacts on quality of life is limited. We conducted an online survey to understand how auditory environments influence the relationships between Autistic traits and impacts on quality of life (iQoL) due to sound sensitivity. We also sought to determine strategies that Autistic people use to navigate auditory sensitivities in daily life. 296 Autistic adults (58.4% women, 15.9% men, 24.3% non-binary +) aged 18–71 years completed the survey comprising a questionnaire with bespoke items measuring auditory experiences in different environments (e.g., noisy vs. quiet) and measures of Autistic traits and iQoL. Our path analyses revealed a significant indirect effect of aversive auditory environments on the relationships between all domains of Autistic traits and iQoL. Notably, the association between non-verbal social communication trait and iQoL was fully mediated by all forms of auditory environments. Additionally, most (n = 217, 73.5%) Autistic participants reported using earplugs and headphones to manage their sound environments in everyday life. Our study demonstrates that many aspects of auditory environments—beyond noise alone―can negatively impact Autistic people’s QoL. Addressing barriers created by auditory environments through accommodations should improve QoL for Autistic people.